Diagnostic Accuracy of MRI in the Detection of Intradural Intramedullary Spinal Tumors - Saeed, Shahzad; Ashraf, Aasma; Hayat, Abdul Malik; Basharat, Rabia; Khan, Muhammad Imran; Nizam, Mehwish (British Journal of Healthcare and Medical Research, 2022)
Objective: To determine the diagnostic accuracy of MRI in the detection of intradural intramedullary spinal tumors taking histopathology as gold standard. Methodology: This study comprised of 140 patients with clinical suspicion of intradural spinal tumor. Magnetic resonance imaging on a 1.5-T Philips whole body magnetic resonance system was performed. The cases were operatedand histopathological results were recorded. The results of magnetic resonance imaging and histopathology were compared taking histopathology as gold standard. Results: Out of 140 patients, 122 patients (87.2%) had an intradural spinal tumor, out of which 26 patients (18.6%) had an intramedullary tumor on MRI. After comparison of results of MRI with histopathology, the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of magnetic resonance imaging were 96.2%, 98.2%, 97.9%, 92.6% and 99.1% respectively. Conclusion: MRI is a highly accurate, non-invasive, safe and convenient imaging modality for the evaluation of intradural spinal tumors and is valuable for early detection, planning management and guiding surgical biopsies.